Analisis Kesalahan Mahasiswa Dalam Menggunakan Teknik Integral Subtitusi Dan Parsial Berdasarkan Newmann’s Error Analysis - Nurrasa, Sidik; Nurrohman, Hidayat (AB-JME: Al-Bahjah Journal of Mathematics Education, 2024)
The purpose of this study was to determine the types of errors in using substitution and partial integral techniques based on Newmann's Error Analysis. This research is a descriptive research. The subjects of this study were three 3rd semester students of the Tadris Mathematics Study Programme at Al-Bahjah Cirebon Islamic Religious College. The instruments used are 4 integral problems of substitution and partial techniques. The results showed that the stages of reading, Process Skill, Transformation, and Encoding errors occurred in the integral question of substitution and partial. This is because students do not understand the concepts of substitution and partial integrals, and cannot apply differential concepts.